2010
DOI: 10.1002/cphc.201000380
|View full text |Cite
|
Sign up to set email alerts
|

1.7 nm Platinum Nanoparticles: Synthesis with Glucose Starch, Characterization and Catalysis

Abstract: Monodisperse platinum nanoparticles (PtNPs) were synthesized by a green recipe. Glucose serves as a reducing agent and starch as a stabilization agent to protect the freshly formed PtNP cores in buffered aqueous solutions. Among the ten buffers studied, 2-(N-morpholino)ethanesulfonic acid (MES), ammonium acetate and phosphate are the best media for PtNP size control and fast chemical preparation. The uniform sizes of the metal cores were determined by transmission electron microscopy (TEM) and found to be 1.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 49 publications
4
23
0
2
Order By: Relevance
“…On Ag NPs modified electrode, peak at 0.4 V in the positive-going scan and 0.3 V in the negative-going scan were observed, corresponding to the oxidation and reduction of Ag and AgO x , respectively, which are in accordance with literature [28]. On Pt NPs modified electrode, the onset potential of hydrogen evolution reaction (HER) was negatively shifted due to the excellent catalytic activity of Pt NPs [29]. Obvious peak at ¡0.3 V corresponding to HER was observed, similar to that of Pt electrode in H 2 SO 4 solution.…”
Section: Anchoring Metal Nanoparticles By Thiol Sam Templatesupporting
confidence: 86%
“…On Ag NPs modified electrode, peak at 0.4 V in the positive-going scan and 0.3 V in the negative-going scan were observed, corresponding to the oxidation and reduction of Ag and AgO x , respectively, which are in accordance with literature [28]. On Pt NPs modified electrode, the onset potential of hydrogen evolution reaction (HER) was negatively shifted due to the excellent catalytic activity of Pt NPs [29]. Obvious peak at ¡0.3 V corresponding to HER was observed, similar to that of Pt electrode in H 2 SO 4 solution.…”
Section: Anchoring Metal Nanoparticles By Thiol Sam Templatesupporting
confidence: 86%
“…Figure A shows a route demonstrated by Kneipp and co‐workers, in which large Au nanospheres and small Pt nanoparticles were separately prepared through the reduction of HAuCl 4 and H 2 PtCl 6 by sodium citrate and glucose/starch, respectively, at elevated temperatures, followed by the simultaneous immobilization of the as‐prepared nanoparticles to form a binary mixture on a solid substrate. Figure B shows a scanning electron microscopy (SEM) image of the binary mixture deposited on a glass slide, revealing both the 40 nm Au nanospheres and less than 2 nm Pt nanocrystals on the surface . Figure C shows a scanning tunneling microscopy (STM) image of the binary mixture deposited on highly ordered pyrolytic graphite (HOPG), confirming the SEM result.…”
Section: Design and Preparation Of Bifunctional Nanocrystalssupporting
confidence: 68%
“…Figure 4 B shows a scanning electron microscopy (SEM) image of the binary mixture deposited on a glass slide, revealing both the 40 nm Au nanospheres and less than 2 nm Pt nanocrystals on the surface. [22,28,29] Figure 4 C shows a scanning tunneling microscopy (STM) image of the binary mixture deposited on highly ordered pyrolytic graphite (HOPG), confirming the SEM result. It was found that continuous scanning of the STM tip would remove some of the Pt nanoparticles, suggesting that these two types of nanoparticles were not strongly linked to each other.…”
Section: Binary Mixture Of Au and Pt Nanocrystalssupporting
confidence: 67%
“…Platinum nanoparticles were synthesized following the saccharide‐based approach for the synthesis of metallic nanostructures (the SAMENS method) in phosphate buffer (pH 9) according to Ref. 12b. Gold and mixed platinum/gold nanostructured surfaces were prepared by immobilization of nanoparticles (particle ratio 1:1 in the mixture) by 3‐aminopropyltriethoxysilane 26…”
Section: Methodsmentioning
confidence: 99%